Design and Simulation of a LAN Network for Optimizing IT Infrastructure at SMKS XYZ Depok Using Cisco Packet Tracer - Thobiyah T; Franciscus, Anre; Fakrurrozi; Wichaksono, Ilyas; Al Baqi, Iqbal Habib; Daeli, Ridwan; Tarigan, Riko (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Reliable and efficient computer network connectivity is essential for supporting the performance of applications and services operating within that network. Cisco Packet Tracer is a simulation tool that facilitates the design and testing of computer networks prior to actual implementation, thereby reducing the risk of errors during deployment. This study designs and evaluates two network scenarios utilizing a star topology connected to a single server, aimed at linking computers within a Local Area Network (LAN) at SMKS XYZ Depok. The design focuses on enhancing network stability and connection speed. The simulation results demonstrate that the star topology provides stable and efficient connectivity within the network environment at SMKS XYZ Depok. Additionally, this study assesses network performance in terms of latency, throughput, and reliability, and identifies areas for potential improvement to further optimize network performance. Thus, this research makes a significant contribution to enhancing the quality of the network infrastructure at the educational institution